INHERITANCE OF CRUDE FAT AND RAW CELLULOSE IN GRAIN SORGHUM HYBRIDS F1 - V. V. Kovtunov; O. A. Lushpina (Зерновое хозяйство России, 2018)
Grain sorghum is basically a forage crop, so a content of nutrients should be controlled during hybridization. Fat is a reserved substance which is considered to be a concentrated energetic and constructional force of a seed. Cellulose is the second significant grain polysaccharide after starch and it’s incorporated into cell walls. Increased content of cellulose in grain reduces nutritious value of forage.  Having analyzed domination degree, calculated by B. Griffing, we determined that cultivars of the first generation of grain sorghum which were hybridized on diallel scheme 4x4 with parent forms ‘Belozernoe 100’, ‘ZSK-4’, ‘34045’ and ‘Otbor 100’, inherited types of crude fat and raw cellulose differently. In the most hybrids we saw average content of crude fat relevant to parent forms. As for content of raw cellulose hybrids of the first generation showed dominance of the larger value of the trait and overdominance.  Despite the overdominance of the trait all the analyzed hybrids had a low content of cellulose (1,52-1,89%).